Resilience and COVID-19. An Analysis in University Students during Confinement - Ángela Serrano Sarmiento; Roberto Sanz Ponce; Aurelio González Bertolín (MDPI AG, 2021)
The COVID-19 pandemic has changed life for millions of people. The social-emotional consequences of the confinement need to be analysed urgently. This study examines self-perceived resilience and its most important determining factors in a sample of university students facing COVID confinement. The measuring instrument used is the Connor-Davidson Resilience Scale, divided into four factors and applied to a sample of 253 graduate and postgraduate students. Different methods of descriptive statistics and statistical hypothesis testing were used to calculate the results with the statistical program SPSS-22. The results showed generally high levels of resilience among the university students analysed, irrespective of socio-demographic variables. Factor analysis shows resilience to be highest among male students and those over 25. Self-perceived resilience was also higher among students who lived alone or with people other than their parents. Finally, students of the health sciences were more likely to adapt to change, deal with today's challenges, and think of themselves as people capable of bouncing back after hardship.